Is Radical Surgery Necessary for All Patients Diagnosed as Having Non-Curative Endoscopic Submucosal Dissection? - Si Hyung Lee; Byung Sam Park (Korean Society of Gastrointestinal Endoscopy, 2019)
If a lesion does not meet the expanded indication criteria for treatment with endoscopic therapy for early gastric cancer or has a positive resection margin, it is regarded as suitable for non-curative resection. Non-curative resection is closely related to the risk of local recurrence, lymph node metastasis, and poor prognosis. If the result is confirmed as non-curative resection, additional treatment should be considered depending on the risks of residual tumor, local recurrence, and lymph node metastasis. As lymphatic invasion is the most important risk factor of recurrence and poor prognosis, surgical treatment should be considered if lymphatic invasion is present. If patients are not suitable for additional surgery owing to old age or coexisting severe disease, close surveillance can be an alternative treatment option.